HST Imaging of New Edge-on Circumstellar Disks in Nearby Star-forming Regions. Issue Volume 8:Issue S299(2013) (6th January 2014) - Stapelfeldt, K.R.; Duchêne, G.; Perrin, M.; Wolff, S.; Krist, J.E.; Padgett, D.L.; Ménard, F.; Pinte, C.
Abstract: Edge-on, optically thick circumstellar disks have been previously imaged at subarcsecond resolution around about a dozen nearby young stellar objects. In these systems the central star is occulted from direct view, bright star image artifacts are absent, and the disk reflected light is clearly seen. Comparison of Hubble Space Telescope (HST) edge-on disk images with scattered light models has allowed key disk structural parameters and dust grain properties to be determined. Edge-on disks have been systematically undercounted to date: while 10% of young stars should statistically be occulted by their disk, the observed frequency is much less. Thus there is a significant potential for discovering and imaging new examples. Spitzer Space Telescope legacy science programs have provided the first good spectral energy distribution (SED) measurements for the previously known edge-on disks. These can be used as templates to identify new candidates in far-infrared survey datasets. We report on the results of our HST program to image twenty-one edge-on disk candidates mostly selected from their SEDs. Eleven are well-resolved with radii ranging from 30-400 AU, nine for the first time and six showing highly collimated jets. Outstanding individual sources include a large and symmetric new template object, a highly flattened disk not accreting onto its central star, and an asymmetric disk with a misaligned jet which likely traces tidal perturbations in a binary system. Follow-up work to obtain ancillary data and perform scattered light modeling of the most symmetric disks is now being pursued. The results of this program will guide a new round of searches for these rare but important snapshots of protoplanetary disk evolution.